Nutritional application software for restaurants: the tool of customer satisfaction and behaviour. (2016) - Palisidis, Georgios; Giazitzi, Katerina; Karathanos, Vaios; Boskou, George
Technological solutions provided to customers with the aim of nutritional information, could be a major challenge of interaction amongst caterers and customers. The purpose of this paper is to evaluate an electronic intelligent system of personalised dietary advice (called 'DISYS') for tablets and smartphones. This application provides nutritional analysis of menu items and personalised suggestions according to the nutritional demands of each customer. The DISYS application was characterised as an easy-to-use, comprehensive and useful tool. Volunteers consider that this application contributes to overall health by enabling the modulation of body weight through healthier choices, reduction of calorie intake and self-monitoring. Application of mHealth as such, designed to provide nutritional information, seems to be useful for customers as they recommend appropriate nutritional options. They seem also to be an effective tool for caterers and nutritionists, who can provide value-added services.